iPhone and iPad app : 24-hour trainer - Mishra, Abhishek; Backlin, Gene (Indianapolis, Indiana : Wiley, 2012)
Annotation An all-in-one tutorial for planning, developing, and launching iPhone and iPad apps. The number of applications in the Apple app store is growing at a staggering rate. With little or no prior programming experience, you can learn the code necessary to build an app with these no-nonsense lessons.
"IPhone and iPad App 24-Hour Trainer"; "Contents"; "Introduction"; "Who This Book Is For"; "What This Book Covers"; "How This Book Is Structured"; "Instructional Videos on DVD"; "Conventions"; "Source Code"; "Errata"; "p2p.wrox.com"; "Chapter 1: Hello iOS!"; "iOS Developer Essentials"; "Try It"; "Chapter 2: The iOS Simulator"; "Features of the iOS Simulator"; "Limitations of the iOS Simulator"; "Chapter 3: A Tour of Xcode"; "The Welcome Screen "; "Selecting a Project Template"; "Setting up Project Options"; "An Overview of the Xcode IDE " "Try It""Chapter 4: iOS Application Basics"; "Application States"; "Windows, Views, and View Controllers"; "Frameworks"; "Creating User Interface Elements "; "Try It"; "Chapter 5: Introduction to Storyboards"; "Try It"; "Chapter 6: Handling User Input"; "Text Fields"; "Text Views"; "Try It"; "Chapter 7: Communicating with Your Users"; "Alert Views"; "Action Sheets"; "Try It"; "Chapter 8: Adding Images to Your View"; "The UIImage Class"; "The UIImageView Class"; "Try It"; "Chapter 9: Pickers"; "Arrays in Objective-C"; "Try It" "Chapter 10: Date Pickers""Dates in Objective-C"; "Try It"; "Chapter 11: Custom Pickers"; "Try It"; "Chapter 12: Navigation Controllers"; "Navigation Controller Interface"; "Navigation Controller Hierarchy"; "Try It"; "Chapter 13: Table Views"; "Table View Workflow"; "Table View Styles"; "New for iOS 5"; "Try It"; "Chapter 14: Static Table Views"; "Table View Types"; "Table View Design"; "Try It"; "Chapter 15: Tab Bars and Toolbars"; "Tab Bars"; "Toolbars"; "XIB-Based Xcode 4.2 Changes"; "Try It"; "Chapter 16: Creating Page-Based Applications" "The PageViewController Class""The Page-Based Application Template"; "Try It"; "Chapter 17: Creating UI Elements Programmatically"; "UIButton"; "UILabel"; "UIImageView"; "Try It"; "Chapter 18: Creating Views That Scroll"; "The UIScrollView class"; " Scroll Views and Text Fields"; "Try It"; "Chapter 19: Popovers and Modal Views"; "Popovers"; "Modal Views"; "Try It"; "Chapter 20: Tweeting with Twitter"; "The Tweet Sheet"; "Try It"; "Chapter 21: Basic File Handling"; "The IOS File System"; "Introducing the NSFileManager Class"; "Object Serialization" "Try It""Chapter 22: Property Lists"; "Property List Types"; "Creating Property Lists"; "Try It"; "Chapter 23: Application Settings"; "Adding a Settings Bundle"; "Reading Preferences with Code"; "Try It"; "Chapter 24: iTunes File Sharing Support"; "Try It"; "Chapter 25: Introduction to iCloud Storage"; "Basic Concepts"; "Preparing to Use the iCloud Storage APIs "; "Checking for Service Availability"; "Using iCloud Document Storage"; "Try It"; "Chapter 26: Introduction to Core Data"; "Basic Concepts"; "Instantiating Core Data Objects"
Includes index.
Keywords: APPLICATION SOFTWARE -- DEVELOPMENT